Mysli o Polsce i Polakach - Nowak, Jerzy Robert, 1940- (Katowice : Wydawn. Unia, 1994)
A collection of statements about the Polish character and trait, with biographies of the personalities who wrote the statements.
Includes bibliographical references and index.
Keywords: National characteristics, Polish; Poland -- Public opinion; Poland -- Foreign public opinion